Bacteriological profile of ready-to-eat food items in Kathmandu - Arjyal, Charu; Manandhar, Sagarika; Dulal, Shraddha (Scientific World, 2024)
Ready-to-eat (RTE) food items are defined as the foods prepared or cooked in advance, with no further cooking or preparation required before being eaten. Consumption of ready-to-eat foods prepared in an unhygienic environment can lead to different types of food-borne illnesses ranging from mild self-limiting ones to severe food poisoning leading to mortality. The goal of this study was to see if the ready-to-eat foods available in Kathmandu was contaminated with bacteria and to determine the antibiotic susceptibility pattern of the isolated bacteria. A total of 100 ready-to-eat foods (momo & sauce, chowmein, pizza, thakali set, burger and samosa) were gathered from various locations around Kathmandu and analyzed by standard microbiological methods in the Microbiology Department of Tri-Chandra Multiple Campus from March to August 2022. Out of 100 samples analyzed, 55 showed the presence of bacteria; Escherichia coli was found to be predominant (52.72%), followed by Bacillus cereus (16.38%) and Salmonella spp (12.72%), among others. Momo and its sauce contained highest number of bacteria, followed by chowmein and burger; the least number of bacteria was found in samosa and pizza. Antibiotic susceptibility test was performed against all isolated bacteria following standard disc diffusion method. The bacterial isolates were sensitive towards Meropenem and Ceftriazone whereas they were resistant towards Ampicillin and Nalidixic acid. One bacterial isolate (Klebsiella pneumoniae) showed Multi Drug Resistance (MDR) which was also an ESBL (Extended Spectrum Beta Lactamase) producer. Significant presence of bacteria in ready-to-eat food items indicate the unhygienic practice of food preparation and handling and can pose threat to the health of general public. It also emphasizes the need for regular monitoring of food items to reduce the risk of food associated illnesses.